2000
DOI: 10.1103/physrevb.62.10852
|View full text |Cite
|
Sign up to set email alerts
|

Many-body theory of pump-probe spectra for highly excited semiconductors

Abstract: We present a unified theory for pump-probe spectra in highly excited semiconductors, which is applicable throughout the whole density regime including the high-density electron-hole BCS state and the low-density excitonic Bose-Einstein condensate (BEC). The analysis is based on the BCS-like pairing theory combined with the Bethe-Salpeter (BS) equation, which first enables us to incorporate the state-filling effect, the band-gap renormalization and the strong/weak electronhole pair correlations in a unified man… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…These theories agree with experimental data for materials that have indirect band-gap or small exciton binding energy [9][10][11]. In wide-gap semiconductors such as GaN, however, excitonic effects are important even in the EHP states [12,13]. Therefore, the correlation effects of excitons and biexcitons on the radiative recombination processes should be considered for highly excited GaN films.…”
supporting
confidence: 69%
“…These theories agree with experimental data for materials that have indirect band-gap or small exciton binding energy [9][10][11]. In wide-gap semiconductors such as GaN, however, excitonic effects are important even in the EHP states [12,13]. Therefore, the correlation effects of excitons and biexcitons on the radiative recombination processes should be considered for highly excited GaN films.…”
supporting
confidence: 69%
“…27 Recently, the authors have shown that, even in very high densities, the e-h pair correlation is enhanced by a strong photoexcitation and the BCS-like gap extraordinarily grows with increasing pump-light intensity. 44 This result suggests a possibility of decisive experimental observation of e-h BCS state under strong photoexcitations. Figure 3 illustrates the e-h pair wave function k ͑Refs.…”
Section: B the E-h Pair Correlation And The Bcs-like Energy-gap Formmentioning
confidence: 92%
“…We analyze the time-independent Hamiltonian in the rotating-frame representation obtained by the Galitskii transformation 33,38,39 that is defined by the following unitary operator:…”
Section: Formulationmentioning
confidence: 99%
“…Later, the analysis has been extended to consider the relaxation processes with the nonequilibrium Green function formalism 34,35 and the interparticle Coulomb interaction. [35][36][37][38][39] However, these results are not conclusive because the BCS-like mean-field theory overestimates the BEG.…”
Section: Introductionmentioning
confidence: 99%